Targeting neurons in the gastrointestinal tract to treat Parkinson's disease. (2019) - Hauser, Robert A.; Sutherland, Dean; Madrid, Juan A.; Rol, Maria Angeles; Frucht, Steven; Isaacson, Stuart; Pagan, Fernando; Maddux, Brian N.; Li, George; Tse, Winona; Walter, Benjamin L.; Kumar, Rajeev; et al.
Abstract: Background: Parkinson's disease (PD) is associated with α-synuclein (αS) aggregation within the enteric nervous system (ENS) and constipation. Squalamine displaces proteins that are electrostatically bound to intracellular membranes and through this mechanism suppresses aggregation of αS monomers into neurotoxic oligomers. Objective: We sought to evaluate the safety of ENT-01 oral tablets (a synthetic squalamine salt), its pharmacokinetics, and its effect on bowel function in PD patients with constipation. Methods: In Stage 1, 10 patients received escalating single doses from 25 to 200 mg/day or maximum tolerated dose (MTD). In Stage 2, 34 patients received daily doses escalating from 75 to a maximum of 250 mg/day, a dose that induced change in bowel function or MTD, followed by a fixed dose for 7 days, and a 2-week washout. Primary efficacy endpoint was defined as an increase of 1 complete spontaneous bowel movement (CSBM)/week, or 3 CSBM/week over the baseline period, as defined by FDA guidelines for prokinetic agents. Safety was also assessed. Results: Over 80% of patients achieved the primary efficacy endpoint, with the mean number of CSBM/week increasing from 1.2 at baseline to 3.6 during fixed dosing ( p  = 1.2 × 10 −7 ). Common adverse events included nausea in 21/44 (47%) and diarrhea in 18/44 (40%) patients. Systemic absorption was <0.3%. Conclusions: Orally administered ENT-01 was safe and significantly improved bowel function in PD, suggesting that the ENS is not irreversibly damaged in PD. Minimal systemic absorption suggests that improvements result from local stimulation of the ENS. A double-blind, placebo-controlled study is now ongoing.